2022
DOI: 10.3390/vaccines10091539
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Vaccination Intention against the COVID-19 Pandemic: A Global Population-Based Study

Abstract: Several vaccines have been developed for COVID-19 since the pandemic began. This study aimed to evaluate the factors associated with COVID-19 vaccination intention. A global survey was conducted across 26 countries from October, 2020 to December, 2021 using an online self-administered questionnaire. Demographic information, socio-economic status, and clinical information were collected. A logistic regression examined the associations between vaccine intention and factors such as perceptions and the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, it is suggested that the government should provide ample information on vaccines to the general public. It is also recommended that vaccination centers be set up in more convenient locations with later service hours to address the difficulty of making time for getting children vaccinated after the long working hours of the parents [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that the government should provide ample information on vaccines to the general public. It is also recommended that vaccination centers be set up in more convenient locations with later service hours to address the difficulty of making time for getting children vaccinated after the long working hours of the parents [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with cancer undergoing active cancer treatment in our center appear to be less reluctant to COVID-19 vaccination than expected. Patients with cancer have been described to be more hesitant to undergo COVID-19 vaccination, as demonstrated by a global population-based study exploring factors associated with vaccination intention against COVID-19, which showed that more patients with a history of cancer in the past 5 years were unwilling to receive vaccination against COVID-19 (61%) vs those without a history of cancer (14%) [22]. A meta-analysis on COVID-19 vaccine acceptance and hesitancy among patients with cancer, including 29 studies, found a pooled prevalence of vaccine acceptance of 59% and a pooled prevalence of vaccine hesitancy due to fear of vaccine-related side-effects of 53% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have largely focused on factors related to the intent to vaccinate rather than the completion of COVID-19 vaccination. A 2022 global, population-based analysis noted that participants identifying as female, in older age groups, with a higher level of education, and with health insurance reported being more willing to get vaccinated [32]. In a study of Latin American and Caribbean countries, those with a university education, residence in an urban area, and a higher perceived likelihood of contracting COVID-19 had higher intentions to be vaccinated [31].…”
Section: Discussionmentioning
confidence: 99%
“…Municipalities are organized into 22 departments, and some variables only available at the departmental level were obtained through the 2014-2015 Demographic and Health Survey [29]. We chose sociodemographic variables a priori that could be proxies for healthcare access, poverty, and related variables that we hypothesized to be related to vaccination uptake [30][31][32]. We elected to use the general poverty indicator (percentage of each municipality population experiencing poverty) developed by Figueroa Chávez and colleagues and shared with our team [33].…”
Section: Methodsmentioning
confidence: 99%